Interculturality and (Post)colonialism: Ethnicity, Nationalism, Cultural Memory and Identity - Gjurgjan, Ljiljana Ina (Array, 2010)
The paper proposes to look into two cases of construction of national/ethnic identity - Irish and American. In doing so, it desires to challenge the stereotypes about European nationalism vs. American multiculturalism by distinguishing between multi and poly cultural societies, in particular in regard to their cultural memory. The Irish sense of national identity is seen as paradigmatic for European postcolonial countries in its production of cultural stereotypes as well as the way in which its cultural memory is recuperated from colonial erasure. American (both Canadian and US) cultural memory differs from this paradigm. Though the word nationalism is sometimes used to describe Afro-American movements, it is the case of ethnic, rather than national identification. However, nationalism is not unfamiliar to American sense of identity as we have seen in the reactions to Sept. 11th or in the case of less aggressive, but equally nationalistic immigration policy in Quebec.